الاستراتيجية الجزائرية في تصدير الغاز الطبيعي خلال الفترة (2009-2020م) - إلياس, زكري; فائزي, الصادق الامين (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الدراسة إلى التعرف على استراتيجيات تصدير الغاز الطبيعي في الجزائر خلال الفترة (2009-2020م) وذلك من خلال الاطلاع على الاحصائيات والأرقام المتعلقة بحجم انتاج واستهلاك وتصدير الغاز الطبيعي في الجزائر، وتحليل البيانات المتاحة، حيث استخدمت هذه الدراسة المنهج الوصفي عن طريق استقراء الدراسات، الأبحاث، الكتب والمقالات العربية والأجنبية المتعلقة بالموضوع، والمنهج التحليلي من خلال تحليل البيانات التي تتوافر عن إشكالية الدراسة وفي إطار الإشارة إلى الواقع العالمي. وقد توصلت هذه الدراسة أن الجزائر تعتبر من اكبر الدول المنتجة والمصدرة للغاز الطبيعي في العالم ويشهد سوق الغز الدولي تذبذبا في أسعاره بالتزامن مع الأزمات الدولية. This study aims to identify strategies for exporting natural gas in Algeria during the period (2009-2020) by reviewing statistics and figures related to the volume of production, consumption and export of natural gas in Algeria, and analyzing the available data. This study used the descriptive approach by extrapolating studies. Research, Arabic and foreign books and articles related to the subject, and the analytical approach by analyzing the data available on the problem of the study and within the framework of referring to the global reality. This study found that Algeria is considered one of the largest producing and exporting countries of natural gas in the world, and the international gas market witnesses fluctuation in its prices in conjunction with international crises.
Keywords: الاستراتيجيات، الغاز الطبيعي، التصدير.; Strategies, Natural gas, Export.